Combined drying of Nopal pads (Opuntia ficus‐indica): Optimization of osmotic dehydration as a pretreatment before hot air drying. Issue 11 (8th September 2019) - Rodriguez, Anabel; Sancho, Ana María; Barrio, Yanina; Rosito, Pablo; Gozzi, Marta Sofía
Abstract: The aim of this work was to optimize the osmotic dehydration (OD) as a pretreatment before hot air drying (HAD) in Nopal pads. A Box–Behnken experimental design was used to optimize the OD conditions with respect to physicochemical and chromatic parameters, and mechanical properties of Nopal pads. Factors studied were: Three concentrations of sucrose (30, 40, and 50°Brix), calcium lactate (1, 2, and3%), and immersion time (1.5, 2.5, and 3.5 hr). Results showed that sucrose concentration and immersion time were the variables with higher influence. Quality properties mentioned before and the final mineral content of the dried samples (at 60°C for 48 hr) were analyzed. The combined drying (OD + HAD) reduced the moisture content in the range of 23% to 30% compared to HAD alone. It was found that the optimization of OD allowed preserving the quality properties, being a good alternative to give an added value for dried Nopal pads. Practical applications: Nopal has important bioactive properties for both humans and animal diets, since it is a rich source of vitamins, minerals, and fibers. However, the main problem of its production is that post harvesting waste is greater than 50%. For this reason, there is a great interest to study inexpensive preservation methods that allow keeping the main attributes of processed fruits. The osmotic dehydration (OD) and the hot air drying (HAD) are two simple and inexpensive techniques which can be applied by both the food industry and small‐scale food producers. In the present study, the optimization of OD as a pretreatment before HAD was a reliable tool to preserve the quality properties of Nopal pads.